Análise da pesquisa científica sobre o controle microbiano de insetos com fungos entomopatogênicos - Guizzi, Andressa (Universidade Federal de São Carlos, 2019)
The continuous growth in agriculture over the years has led to the proliferation of pest insects in crops. Faced with this issue, various biological control programs have been implemented, including microbial control of insects, an alternative method that uses microorganisms such as entomopathogenic fungi to combat pest species. With the increasing number of research studies over the years, a bibliometric analysis was conducted to examine the rapid scientific development in the field of microbial control of insects with entomopathogenic fungi worldwide and Brazil, covering the period from 2000 to 2019. The databases Scopus®, Google Scholar®, and SciELO® were utilized, identifying 2,382 articles worldwide and 300 studies in Brazil, with a significant increase in publications from the early 21st century. The countries that stood out the most in terms of scientific publications were the USA, Brazil, and China, with the Southeast region being the most productive among the Brazilian regions. Prominent educational and research institutions in Brazil were USP and EMBRAPA, leading the rankings. A direct relationship was observed between the number of articles published in countries and Brazilian regions and the affiliated educational and research institutions of the authors.
Analysis of scientific research on the microbial control of insects with entomopathogenic fungi
Keywords: Insetos-praga; Entomopatógenos; Bibliometria; Produção científica; Crop insects; Entomopathogens; Bibliometrics; Scientific production; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE